Pengaruh Harga, Kebersihan Lingkungan dan Variasi Produk terhadap Minat Beli Masyarakat pada Pedagang Kuliner di Rest Area Tongas - Eko Wicaksono (Departement of Mathematics Education, 2021)
This study aims to determine the effect of price, environmental cleanliness, and product variety on people's buying interest in culinary traders in the Tongas Rest Area. The research uses a quantitative descriptive research method which is carried out through data collection with primary and secondary data. The data analysis technique in this study is the classical assumption test and multiple linear regression analysis. The results of the study show that the price (X1) has increased by one unit, then buying interest (Y) will have increased by 0.434 = 43.4%, the coefficient is positive, meaning that price and buying interest have a positive relationship. environmental cleanliness (X2) has increased by one unit, then buying interest (Y) will have increased by 0.197 = 19.7%, the coefficient is positive, meaning that environmental cleanliness and buying interest have a positive relationship. Product variety (X3) has increased by one unit, then buying interest (Y) will have increased by 0.132 = 13.2%, the coefficient is positive, meaning that product variation and buying interest have a positive relationship.